A review of the potential applications of propolis as natural additive in the Malaysian poultry industry - Lukas, Louisiana Lulu; Latif, Nurfazila; Hassan, Mohammad Nasir; Latif, Kamil; Abit, Lirong Yu; Mustafa, Suhaili; Mohammad Ali Hanafiah, Mohammad Hakim; Thlama, Paul Bura; Pertiwi, Herinda; Al-Twain, Sarah; Kamaludeen, Juriah (Malaysian Society of Applied Biology, 2023)
Antibiotics are used in the poultry industry as feed additives to improve growth, prevent disease, treat sick animals, stabilize intestinal microflora and improve growth performance. Due to the risks regarding long term antibiotic resistance development of pathogentic bacteria in humans, the utilization of synthetic antimicrobials in livestock feed has been banned in most animal production practices. However, antibiotic prohibition in livestock can result in poor performance of the animals in term of yield of production, quality and health status. Therefore, it is important to find natural alternatives such as propolis to substitute for antibiotic usage in livestock feed. Propolis is a natural resin produced by honeybees. There are over 300 beneficial compounds found in propolis. It contains various bioactive compounds such as flavonoids, phenolic acids, and among others which contribute to its antimicrobial, antifungal and antioxidant properties. Various studies have been carried out to determine the biological and chemical activities of propolis as well as its function as an alternative natural feed additive. Thus, this review focuses on propolis composition, the potential of stingless bee propolis in Borneo, its potential as an antioxidant with antimicrobial properties and the potential of propolis as a natural feed additive for poultry.